Pharmacodynamic interaction of green tea extract with hydrochlorothiazide against ischemia-reperfusion injury-induced myocardial infarction - Manodeep Chakraborty; Jagadish Vasudev Kamath (Wolters Kluwer Medknow Publications, 2014)
Globally, the rate of development of myocardial diseases and hypertension is very common, which is responsible for incremental morbidity and mortality statistics. Treatment of ischemic hypertensive patients with diuretics such as hydrochlorothiazide (HCTZ) can precipitate myocardial infarction due to hypokalemia. This study was undertaken to evaluate the pharmacodynamic interaction of green tea extract (GTE) with HCTZ against ischemia-reperfusion induced myocardial toxicity. Wistar albino rats of either sex were taken and pretreated with high (500 mg/kg, p.o.) and low (100 mg/kg, p.o.) dose of GTE for 30 days. Standard, high and low dose of interactive groups received HCTZ (10 mg/kg, p.o.) for last 7 days. Ischemia-reperfusion injury was induced by modified Lagendorff apparatus, and the effect of different treatments was evaluated by percentage recovery in terms of heart rate and developed tension, serum biomarkers, and heart tissue antioxidant levels. Prophylactic treatment groups, such as high and low dose of GTE and their interactive groups with HCTZ, exhibited significant percentage recovery in terms of heart rate and developed tension. Apart from that, significant increase in superoxide dismutase and catalase, decrease in thiobarbituric acid reactive species in heart tissue, as well as significant decrease in serum lactate dehydrogenase, creatinine phosphokinase-MB and N-acetylcysteine levels have also been documented. The present findings clearly suggest that GTE dose-dependently reduces myocardial toxicity due to ischemia, and combination with HCTZ can reduce the associated side-effects and exhibits myocardial protection.